Ferroferric Oxide Significantly Affected Production of Soluble Microbial Products and Extracellular Polymeric Substances in Anaerobic Methanogenesis Reactors - Yin, Qidong; He, Kai; Echigo, Shinya; Wu, Guangxue; Zhan, Xinmin; Hu, Hongying (Frontiers in Microbiology, 2018)
Conductive materials facilitate direct interspecies electron transfer between acidogens and methanogens during methane (CH4) production. Soluble microbial products (SMP) and extracellular polymeric substances (EPS) produced by microorganisms might act as the electron shuttle between microorganisms and conductive materials. In this study, effects of conductive ferroferric oxide (Fe3O4) on anaerobic treatment process and the production of SMP and EPS were investigated. The maximum CH4 production rate was enhanced by 23.3% with the dosage of Fe3O4. The concentrations of proteins, polysaccharides and humic substances in tightly bound EPS (T-EPS) was promoted, suggesting that extracellular metabolisms were induced by conductive materials. Distribution of potential electron shuttles such as quinone-like substances, flavins, aromatic amino acids and dipeptides in SMP and EPS phases were comprehensively investigated and these electron shuttles were significantly affected by Fe3O4. Dipeptides consisting of phenylalanine were widely detected in T-EPS of the Fe3O4 reactor, indicating a potential different extracellular electron exchange pattern with the addition of conductive materials.